Pengaruh PhytoRemediator Tanaman Kayu Apu (Pistia stratiotes) dan Kiambang (Salvinia molesta) pada Kualitas Air Graywater untuk Hidroponik Tanaman Selada (Lactuca sativa) - Oteng Haridjaja; Wahyu Purwakusuma; Ratih Safitri (Jurnal Sains Terapan : Wahana Informasi dan Alih Teknologi Pertanian, 2011)
Graywater of domestic waste has a  biodegradable organic matter characteristics which can be decreased by using waterwaste phytoremediator method. The objective of this research was to study the effect of Pistia Stratiotes and Salvinia Molesta on water quality for hydrophonic media of Lactuca Sativa production. Greenhouse experiments were conducted at Darmaga Research Station, Bogor. A complete factorial experimental design with three replications was used. The first factor was two waterwaste circulation remediator tank types (WWCRTT), and the second factor was a control, Pistia and Salvinia treatments.  The results of these experiments showed that:  the influence of plant has a significant difference to water COD at zero to one week after planting(WAP), and the influence of WWCRTT has also a significant difference to water COD at three WAP. The influence of WWCRTT has a significant difference to P-water content at zero, two, and three WAP. Plants, WWCRTT and their combinations have significant diference on NO3-water content at one WAP. The total of P and NO3 water contents were not sufficient for plant growth, and the influence of  flooding water and bad drainage can decrease plant yield.Key words: graywater, hydrophonic, phytoremediator